'Canalization' of the frontal sinus: a functional approach for the management of post-traumatic sinusitis with lateral bony septa. Report of two cases and long-term follow-up. Issue 7 (July 2016) - Foy, J.-P.; Khonsari, R.H.; Bertolus, C.; Espitalier, F.; Ferron, C.; Corre, P.; Faure, A.
Abstract: The patency of the naso-frontal duct is a key issue in the surgical management of chronic frontal sinusitis. Most of the current operative techniques only provide access to the paramedian portions of the frontal sinus. A canalization approach that allows a functional frontal sinus to be maintained while providing good access to the most lateral areas of the sinus is described herein. Two cases of severe post-traumatic frontal sinusitis, operated on successfully by canalization method based on the conservation of the frontal sinus and the maintenance of the patency of the naso-frontal duct, using both open and endonasal approaches, are reported. One patient was followed-up for 8 years and the other for 7 months. Canalization requires validation in a larger series. This approach provides an alternative to both cranialization and strictly endoscopic methods in lateralized frontal sinus retentions and allows mucocele to be avoided.